PERAN PENULISAN KARYA ILMIAH DAN PTK BAGI PROFESIONALISME GURU SENI BUDAYA - Trisakti Trisakti; Anik Juwariyah; Setyo Yanuartuti; Warih Handayaningrum (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
The background for conducting the training comes from the teachers need in fulfilling the obligation tocompose scientific works for job promotion matters and teachers achievement documentation. Thisactivity is aimed at improving the understanding and the skills of Arts and Culture teachers in composingscientific works and Classroom Action Research through training. Furthermore, it was carried out throughlecture, discussion, task giving and guidance. The results of the questionnaire showed thatthe ability of theparticipants in composing the Classroom Action Research is 92% very good. Also, with regard tocomposing the Classroom Action Researchand scientific works, it was found that based on the aspect ofunderstanding the contents of the materials presented, the ability of the participants reaches 84,6%percentage. Besides, the easinessof generating ideas in writing Classroom Action Research achieves69%, while the ability of developing Classroom Action Research writing well obtains 69%. In addition, theresponse onthe Classroom Action Research aspect supporting the learning process is 61,5%. Meanwhile,opinion on the Classroom Action Research donethat can be applied gets 69% percentage. The averagescore of the participants in writing proposal is 78. In general, the average score is satisfactory, consideringthat there were some participants who previously did not understand aboutClassroom Action Researchbecause their specialty ispure art. Additionally, the percentage of the participants achieving score above70 is 69%, while the rest 30% got 60 and below. It indicates that the trainingonscientific works andClassroom Action Research writing has been successlly run and shown a noticable result.